Coverage probability of multiple UAVs supported ground network. Issue 13 (1st June 2017) - Guo, Zijun; Wei, Zhiqing; Feng, Zhiyong; Fan, Ning
Abstract : In disaster recovery, ground network consisting of mobile terminals of rescue vehicles and civilians may be disconnected due to severe environment. In this situation, multiple unmanned aerial vehicles (UAVs) form an aerial network to enhance the connectivity of the ground network. When two nodes in ground network are disconnected, they adopt UAVs as relays to transmit data. Otherwise, they communicate with device‐to‐device manner. With this framework, the coverage probability of these two kinds of users is analysed. Besides, the optimal altitude of UAVs to maximise the capacity of ground network is achieved. A guideline is provided for the design of multiple UAVs support wireless network.